The Importance of Empowering Farmers to Make Compost in an Effort to Improve the Quality of Agriculture Products in Titi Payung - Br Ginting, Dewi Sartika; Saleh, Elnada Nadhira; Luftia, Rifda; Dahri, Imanda Rahmatika; Damanik, Samuel Piscesco; Siahaan, Fereen Tasya Maharani (Talenta Publisher, 2023)
Titi Payung Village is one of the villages in Air Putih District, Batu Bara District, North Sumatra Province. The Titi Payung area has an area of ​​165 hectares, 100 hectares for residential areas and 59 hectares of productive agricultural land. There are a total of 2,551 people there, divided into 6 hamlets. The large amount of agricultural land in Titi Payung Village has an impact on the many Titi Payung Village people who choose to become farmers as their main livelihood. In 2010, the increase in market demand for local agricultural products reached 60%. For this reason, organic fertilizers are needed, especially compost which is more environmentally friendly and can improve the quality of agricultural products. The implementation method used is lectures and demonstrations by inviting farmers to practice directly. The result of the implementation of the activity is an increase in farmer's knowledge regarding the manufacture of good and correct compost. It can be concluded that real work lecture activities can increase the knowledge of farmers in Titi Payung Village regarding the importance of using compost to improve agricultural quality.